Towards a taxonomy for crypto assets - John Fry; Olamide Ibiloye (Cogent Economics & Finance, 2023)
We explore the taxonomy of cryptocurrencies and integrate our analysis with traditional ways of understanding financial assets. We thus classify cryptocurrencies using the time series and distributional properties of returns. Cryptocurrencies appear inherently speculative in nature. The result is even more clear cut when time series measures of distance are used. Results tally with wider concerns raised regarding excessive volatility of stablecoins.
Keywords: C1; G1; G3; 330; Bitcoin; cryptocurrency; fin tech; probability distribution; statistics; time series